2020
DOI: 10.7759/cureus.8360
|View full text |Cite
|
Sign up to set email alerts
|

Plasmapheresis Treatment of Hypertriglyceridemia-Induced Acute Pancreatitis: A Case Report

Abstract: Hypertriglyceridemia is the third most common etiology for acute pancreatitis (AP), after alcohol and gallstones. Clinical evidence is relatively weak in its support of plasmapheresis for the treatment of hypertriglyceridemia-induced acute pancreatitis (HTG-AP). We report a case of severe HTG-AP in a young man who was successfully treated with plasmapheresis. The patient achieved full resolution of symptoms within 48 hours from presentation and was discharged two days later. To our knowledge, no other report i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…However, hypertriglyceridemia, although less frequent, is a recognized cause, occurring in approximately 2-4% of cases. 1 Triglycerides, essential components of fats, are either synthesized in the liver or obtained from the diet. In normal conditions, circulating triglycerides are metabolized into free fatty acids by an enzyme called lipoprotein lipase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, hypertriglyceridemia, although less frequent, is a recognized cause, occurring in approximately 2-4% of cases. 1 Triglycerides, essential components of fats, are either synthesized in the liver or obtained from the diet. In normal conditions, circulating triglycerides are metabolized into free fatty acids by an enzyme called lipoprotein lipase.…”
Section: Discussionmentioning
confidence: 99%
“…It occurs when high levels of triglycerides in the blood lead to inflammation of the pancreas. 1 Treating HTG-induced pancreatitis involves reducing serum triglyceride levels to less than 500 mg/dl promptly since the risk of pancreatitis significantly rises when levels exceed 1,000 mg/dl. [3][4][5] Factors such as poorly controlled diabetes, alcohol consumption, certain medications, and genetic factors can contribute to this condition as they affect lipid metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Another case study reported a similarly rapid reduction in TG levels after plasmapheresis for HTGP; the patient was discharged in a stable condition less than 96 h after initial admission. 11…”
Section: Discussionmentioning
confidence: 99%
“…Another case study reported a similarly rapid reduction in TG levels after plasmapheresis for HTGP; the patient was discharged in a stable condition less than 96 h after initial admission. 11 Studies on the effects of plasmapheresis in HTGP generally report improvement in symptoms and laboratory tests. Limited data is available regarding its impact on pancreatitis severity, such as organ failure and local complications.…”
Section: Discussionmentioning
confidence: 99%